Physicochemical Properties and Antibacterial Activity of Gellan Gum Incorporating Zinc Oxide/Carbon Nanotubes Bionanocomposite Film for Wound Healing - Jichao Liu; Nur Arifah Ismail; Mahani Yusoff; Mohd Hasmizam Razali (Bioinorganic Chemistry and Applications)
Wound healing dressing based on a natural polymer of gellan gum incorporating zinc oxide nanoparticles and multiwall carbon nanotubes (GG/ZnONP + MWCNT) bionanocomposite film was fabricated via the solution casting method. The physicochemical properties of the film were characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR), and scanning electron microscopy (SEM). Moreover, the antibacterial properties of the bionanocomposite film were investigated for wound healing applications. The characterization results confirmed the reinforcement of the gellan gum (GG) matrix with zinc oxide nanoparticles (ZnONP) and multiwall carbon nanotubes (MWCNT), as an amorphous GG/ZnONP + MWCNT bionanocomposite film was obtained. SEM morphological analysis shows that the addition of ZnONP and MWCNT nanofillers changed the film microstructure into a sponge-like structure that is more suitable for fluid uptake and thus more useful for wound healing. The GG/ZnONP + MWCNT bionanocomposite film demonstrated good antibacterial activity against all strains tested. Furthermore, macroscopic analysis shows that the wound treated with GG/ZnONP + MWCNT bionanocomposite film recovered completely (100%) in 14 days, compared to pure GG film (90.76%) and negative control (77.40%). As a result, the GG/ZnONP + MWCNT bionanocomposite film could be a promising wound dressing material.